دور ريادة الاعمال في تنمية المؤسسات الصغيرة و المتوسطة دراسة ميدانية الوادي المغير - طالب فاطمة; بوحفص ام الخير; مشري نبيلة (جامعة الوادي University Of Eloued, 2025)
" تناولت الدراسة دور ريادة الأعمال في تنمية المؤسسات الصغيرة والمتوسطة، وتمثلت مشكلة الدراسة فيمدىمساهمة ريادة الأعمال في تنمية المؤسسات الصغيرة والمتوسطة، حيث أن ريادة الأعمال والمشروعات الصغيرة والمتوسطة لم تتبلور بعد بشكل كافٍ في هذه المنظمات التي تساهم في زيادة الدخل القومي لما لها من أهمية في توفير الوظائف والأعمال والخدمات. هدف البحث إلى إبراز مفهوم ريادة الأعمال وتوضيح مفهوم المؤسسات الصغيرة والمتوسطة وإبراز دور ريادة الأعمال. استخدمنا منهج الوصف التحليلي الذي يقوم بوصف الظواهر والأحداث، حيث وزع الاستبيان على 53عينة من المشاريع الصغيرة والمتوسطة لولايتي الوادي و المغير ، كما تم تحليل الاستبيانات باستخدام برنامج SPSS، بالإضافة إلى استخدام أسلوب التحليل الإحصائي واختبار الفروض. توصلت الدراسة إلى عدة نتائج منها: أوضحت الدراسة أهمية ريادة الأعمال في دعم وتنمية المؤسسات الصغيرة والمتوسطة أثبتت الدراسة وجود علاقة إيجابية بين تطبيق مبادئ ريادة الأعمال وتحقيق التنمية في هذه المؤسسات "The study examined the role of entrepreneurship in the development of small and medium enterprises (SMEs). The research problem focused on the extent to which entrepreneurship contributes to the development of small and medium enterprises, as entrepreneurship and small and medium projects have not yet been sufficiently crystallized in these organizations that contribute to increasing national income due to their importance in providing jobs, businesses, and services. The research aimed to highlight the concept of entrepreneurship, clarify the concept of small and medium enterprises, and demonstrate the role of entrepreneurship. We used the analytical descriptive method that describes phenomena and events, where a questionnaire was distributed to 53 samples from small and medium projects in the states of El Oued and El Meghaier. The questionnaires were analyzed using SPSS software, in addition to using statistical analysis methods and hypothesis testing. The study reached several results, including: • The study demonstrated the importance of entrepreneurship in supporting and developing small and medium enterprises • The study proved the existence of a positive relationship between applying entrepreneurship principles and achieving development in these enterprises.
ماستر
Keywords: ريادة الأعمال; الابتكار; الاستباقية; المخاطرة; الوكالة، المقاولاتية: Entrepreneurship; Small and Medium Enterprises; Innovation; Proactiveness; Risk-taking; Agency; Entrepreneurialism.